If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3n = 1 + 4n Solving 7 + 3n = 1 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 7 + 3n + -4n = 1 + 4n + -4n Combine like terms: 3n + -4n = -1n 7 + -1n = 1 + 4n + -4n Combine like terms: 4n + -4n = 0 7 + -1n = 1 + 0 7 + -1n = 1 Add '-7' to each side of the equation. 7 + -7 + -1n = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -1n = 1 + -7 -1n = 1 + -7 Combine like terms: 1 + -7 = -6 -1n = -6 Divide each side by '-1'. n = 6 Simplifying n = 6
| 1/6b=16 | | (3x+5)(x-7)=6x+10 | | 5x-4+2(3x+1)=-7(x+2) | | 8x+2x=12+6x | | 6(x+8)=4(x+5) | | 2x^2-62x+468=0 | | 2x^2+12x-56=0 | | 11n=44 | | -5(4n+2)=-90 | | 2(5x+5)-8=82 | | 12x-14=22 | | -5=5+3a-4 | | 186=-5(6+6k)+3k | | 8v-3v=10 | | x^2+23=-22x | | 8x(5-x)= | | 2(w-8)-5=-3(-7w+9)-7w | | 1/4(4)^2x+1=5 | | 163=4(1+5p)-1 | | 5(c+4/5) | | 69=x-.23x | | 100=3(5-7n)+1 | | 4x-16=-22 | | 26=-2(r-6)-6(1-r) | | 4x^2-124x+468=0 | | 26=-2r+12+(-6)+(-6r) | | 2x-25=11 | | -4x-2x+11=6x-13 | | -r^2=49-14r | | 1/2(x+3)=5 | | t=2h-2g | | 780=4t^2+7t+600 |